Consumer Tribe dan Industri Gaya Hidup di Bandung, Indonesia - Soeriaatmadja, Keni (Jurnal Keamanan Nasional, 2017)
In 2015, UNESCO rewarded Bandung as one of the World’s Creative Cities for the ‘design’ category. This raised many reactions from the public, including ones questioning the emergence and existence of communities that play the main role in the creative industry of the city. One of the most significant roles comes from the youth culture in the city which produces goods as part of their lifestyles that has become economically successful and is claimed to be the actors of the creative industry in Bandung, and in Indonesia in a bigger scheme. The fact is, many of these companies emerge from the diffusion of globalization into the youth culture which at some point creates the need to reproduce its cultural icons and symbols into items with more reasonable pricing. The youth culture and its lifestyles then construct a mutual relationship, between producers and consumers, to support this act of reproduction which is unique because it involves the sharing of idealisms. From the perspective of the consumer tribe, this article tries to unfold the historical journey of Bandung’s youth culture and relates it with the social process that occurs within its economic significance.